Terns of endearment - Andrews, Donna (Andrews, Donna. Meg Langslow mysteries., 2020)
Meg's grandfather has been booked to give lectures on a cruise as part of the education/entertainment itinerary, and he's arranged for a passel of family members to join him. The passengers' vacation quickly becomes a nightmare when they wake up to find themselves broken down and in need of repairs. Things get even worse when a crew member announces to all that a woman has jumped overboard, leaving behind her shoes, shawl, and a note. The note reveals she's a disliked member of a writers' group on board for a retreat, and the group is split on whether this is in-character for her. The captain decides not to investigate, saying he'll notify American authorities when they reach their destination. But Meg's father decides they need to look into whether there was possible foul play while the prime suspects are all stuck on board. It'll be a race against the clock to solve this mystery before they make the necessary repairs and return to shore.